Implementasi Internet of Things pada Ruangan Pengujian Kebocoran Ban - Ojak Abdul Rozak; Anto Carmanto; Awaluddin Saputra; Taufik Prasetio (Jurnal Informatika Universitas Pamulang, 2023)
The quality of products resulting from the production process as well as materials for production processes on a large scale can be determined by testing techniques. In the testing process, room temperature is a parameter that needs attention. Many factors affect room temperature such as building construction, weather from outside and the number of people. Room temperature plays an important role and greatly influences the quality and results of the test. In the process of testing for tire leaks, it is carried out in a cold room. Temperature, humidity and air pressure are the parameters in the testing phase. In this case it is necessary to monitor and control especially the temperature so that it remains normal according to the test specifications. In this study, a system was created that can monitor temperature, humidity and air pressure as well as control temperature in IoT-based air conditioners. The aim is to increase user effectiveness in monitoring and controlling towards industry 4.0. This IoT device is made using a process system in the form of a NodeMCU ESP8266 microcontroller, BME280 sensor, and KY-005 IR Transmitter. The method used is by using a black box. The test results from the BME280 sensor compared to the MHB-382SD Thermohygrometer obtained a difference of 0.32 °C for temperature, 3.91% for humidity levels and 0.48 hPa for air pressure. Testing the IR Transmitter KY-005 succeeded in sending a signal to the air conditioner receiver with a distance of less than 7 meters.